Inhibition of sodium release from Zhundong coal via the addition of mineral additives: A combination of online multi-point LIBS and offline experimental measurements. (15th January 2018) - Liu, Yingzu; Wang, Zhihua; Lv, Yu; Wan, Kaidi; He, Yong; Xia, Jun; Cen, Kefa
Abstract: The retention performance of 5 different sorbent additives, including 2 pure additives, i.e., silica and alumina, and 3 typical natural mineral additives, i.e., kaolin, mica and pyrophyllite, on the release of sodium during the combustion of Zhundong coal is investigated via a combination of online multi-point Laser-Induced Breakdown Spectroscopy (LIBS) technique and offline measurements including inductively coupled plasma atomic emission spectrometer (ICP-AES), X-ray diffraction, and ash fusion temperatures (AFTs). The online and offline measurement results for the sodium release of Zhundong coal/additives mixtures are compared and verified with each other. Ternary phase diagram simulations are performed to further substantiate the impact of different additives on liquidus temperatures of Zhundong coal ash. All the five sorbent additives show a significant sodium retention effect, while alumina and kaolin are better additives considering the effects on AFTs.